Structural and Chemical Analysis of Nanoscale Resistive Switching Devices: Assessment on Nonlinear Properties. Issue 1805 (27th August 2015) - Norris, Kate J.; Yang, J. Joshua; Kobayashi, Nobuhiko P.
ABSTRACT: Investigation into the phenomenon of resistive switching, a reversible change in electrical resistance by the application of a voltage bias, has given rise to the device fabrication, DC electrical testing, and cross sectional TEM/EELS characterization of nanoscale resistive switching devices. Typically, resistive switching devices are composed of a thin oxide layer between two conductive electrodes where applied bias can alter the resistance states. In a cross-bar array, nonlinearity of device I-V relation is a highly desirable characteristic that helps to mitigate the sneak path current leakage issue. Negative differential resistance (NDR) switching behavior offers such nonlinearity and has been observed in TaOx nanoscale devices utilizing certain electrode materials. To investigate this phenomenon, nanodevices were fabricated by sputtering TaOx onto TiN nanovias capped Nb electrodes. Cross sectional TEM/EELS were performed to reveal the physical and chemical changes in these devices to explore possible origins of nonlinear behavior when these top electrode materials are utilized with TaOx films.